The Influence Factors Of Tax Avoidance In Indonesia - Ayu Novitasari; Hetty Muniroh (Jurnal Ekuilnomi, 2025)
In early 2020, Indonesia experienced a COVID-19 outbreak that even threatened the stability of the global economy. This also affected corporate tax payments. Tax avoidance measures were taken as a form of anticipation by companies facing the economic crisis. This study aims to investigate how profitability, leverage, independent commissioners, and capital intensity on tax avoidance. The Cash Effective Tax Rate (CETR) is used to measure tax avoidance. The research employs secondary data collected through documentation methods. A purposive sampling method is applied. A total of 27 companies were selected as the sample, resulting in 81 observations. Classical assumption tests were conducted prior to analysis, which was performed using the SPSS program to test the multiple data analysis methods. The results indicate that leverage and independentAcommissioners have a positive but insignificant consequence on tax avoidance; profitability also shows a positive but insignificant impact. Meanwhile, capital intensity and independentB commissioners have a negative but insignificant result on tax avoidance. This research concludes that leverage is a variable that significantly affects tax avoidance